2013
DOI: 10.1155/2013/953520
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofNigella sativaandLepidium sativumon Cyclosporine Pharmacokinetics

Abstract: The present study was conducted to investigate the effects of Nigella sativa and Lepidium sativum on the pharmacokinetics of cyclosporine in rabbits. Two groups of animals were treated separately with Nigella sativa (200 mg/kg p.o.) or Lepidium sativum (150 mg/kg p.o.) for eight consecutive days. On the 8th day, cyclosporine (30 mg/kg p.o.) was administered to each group one hour after herbal treatment. Blood samples were withdrawn at different time intervals (0.0, 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 6.0, 8.0, 12, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Besides improving the intestinal permeability, the fatty acids of black cumin (especially eicosadeinoic acid) were found to inhibit the P-gp activity in silico against the primary amino acid sequence of P-gp from rats leading increased bioavailability of drugs ( 56 ). Contrary to in silico analysis, black cumin is associated with the activation of intestinal P-gp and/or CYP3A4, due to its ability to decrease the bioavailability of cyclosporine (cyclic polypeptide used as immunosuppressant in organ transplantation) in coadministration ( 57 ). Black cumin induced no significant effect on the theophylline pharmakokinetics in Beagle dogs indicating its lack of affinity to CYP1A2 activity; meanwhile fenugreek and garden cress decreased the bioavailability ( 58 ).…”
Section: Selected Herbal Bioenhancersmentioning
confidence: 99%
“…Besides improving the intestinal permeability, the fatty acids of black cumin (especially eicosadeinoic acid) were found to inhibit the P-gp activity in silico against the primary amino acid sequence of P-gp from rats leading increased bioavailability of drugs ( 56 ). Contrary to in silico analysis, black cumin is associated with the activation of intestinal P-gp and/or CYP3A4, due to its ability to decrease the bioavailability of cyclosporine (cyclic polypeptide used as immunosuppressant in organ transplantation) in coadministration ( 57 ). Black cumin induced no significant effect on the theophylline pharmakokinetics in Beagle dogs indicating its lack of affinity to CYP1A2 activity; meanwhile fenugreek and garden cress decreased the bioavailability ( 58 ).…”
Section: Selected Herbal Bioenhancersmentioning
confidence: 99%
“…A similar study, using tolbutamide as a substrate, showed that its oil extract had considerable inhibitory effects against CYP2C11 (Korashy et al 2015). However, when N. sativa was co-administered with cyclosporine in an animal model, the oral bioavailability of cyclosporine was significantly reduced, suggesting the possibility that N. sativa induced intestinal P-glycoprotein and/or hepatic CYP3A activity (Al-Jenoobi et al 2013). Another study presented that the dietary dose of TQ substantially modulate the activity of hepatic xenobiotic metabolizing enzyme in rabbits (Elbarbry et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the C max and AUC 0−∞ of cyclosporine (30 mg/kg) significantly decreased by 35.5% and 55.9%, respectively, after pretreatment with Nigella (200 mg/kg). However, a significant increase in cyclosporine clearance (~2-fold) was observed, thus suggesting that intestinal P-gp and/or CYP3A4 are activated in the presence of N. sativa [144].…”
Section: Oral Route Of Administrationmentioning
confidence: 99%